Laparoscopic appendectomy in complicated appendicitis: Is it safe? - Mohamed, Ashraf A (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Because of lack of good evidence supporting laparoscopic approach for complicated appendicitis, we carried out this study to evaluate efficacy of laparoscopic appendectomy (LA) in management of patients with complicated appendicitis. MATERIALS AND METHODS: This study was carried out in Surgical Department, Minia University, Egypt involving 214 patients underwent appendectomy for complicated appendicitis over three years. 132 patients underwent LA and remaining 82 patients underwent OA. Parameters studied included operating time, return to oral feeding, postoperative pain, wound infection, intra-abdominal abscess, duration of abdominal drainage and hospital stay. RESULTS: There were four conversions, two due to extensive cecal adhesions and two due to friable appendix. LA took longer time to perform (p = 0.0002) but with less use of analgesics (p < 0.0001), shorter hospital stay (p < 0.0001), shorter duration of abdominal drainage (p < 0.0001) and lower incidence of wound infection (p = 0.0005). Nine patients in LA and seven patients in OA group developed intra-abdominal abscess treated successfully with sonographic guided percutaneous drainage. Postoperative ileus was recorded in two patients in LA group and three patients in OA group, chest infection in one patient in OA group, hernia in one patient in LA and fecal fistula was present in one patient in OA. Overall complications were significantly lower in laparoscopy group and managed conservatively with no mortality in either group. CONCLUSIONS: LA in complicated appendicitis is feasible and safe with lower incidence of complications than OA and should be the initial choice for all patients with complicated appendicitis.